Public Sentiment Analysis of the Israel-Palestine Conflict on Social Media Using BERT: Analisis Sentimen Publik Konflik Israel-Palestina di Media Sosial Menggunakan BERT (Indonesian Journal of Cultural and Community Development, 2024)
General background Israel-Palestine conflict has drawn significant global attention, particularly in how it is perceived and discussed on social media platforms. Specific background understanding public sentiment surrounding such geopolitical issues is crucial for media monitoring, diplomatic efforts, and reputation management. Knowledge gap previous sentiment analysis studies often lack the ability to accurately handle multilingual and context-rich datasets, especially in analyzing neutral sentiments, which are commonly overlooked. This study aims to apply the Bidirectional Encoder Representations from Transformers (BERT) model to analyze public sentiment towards the Israel-Palestine conflict on the X platform, focusing on Indonesian users. Results Using BERT, the model achieved 93% accuracy, with a precision of 0.95, recall of 0.93, and F1-score of 0.94. The model performed well in predicting positive and negative sentiments but showed room for improvement in handling neutral sentiment. Novelty this study introduces the implementation of the BERT Transformer model for the multilingual and context-sensitive sentiment analysis of tweets, specifically addressing a high-stakes geopolitical conflict. Implications the findings demonstrate the potential for using advanced natural language processing techniques like BERT for monitoring public opinion, brand management, and detecting societal tensions on social media, offering valuable insights for stakeholders involved in conflict resolution and diplomatic strategies.Highlights: • Achieved 93% accuracy in sentiment analysis using BERT on X platform.• Identified strengths in predicting positive/negative sentiments, with challenges in neutral sentiment.• Demonstrated BERT’s effectiveness in handling complex geopolitical social media data.Keywords: Sentiment Analysis, BERT Transformer, Israel-Palestine Conflict, Social Media, NLP